How do measurement duration and timing interact to influence estimation of basal physiological variables of a nocturnal rodent? - Connolly, M.; Cooper, Christine (Elsevier Inc., 2014)
Metabolic rate and evaporative water loss are two commonly measured physiological variables. It is therefore important, especially for comparative studies, that these variables (and others) are measured under standardised conditions, of which a resting state during the inactive phase is part of the accepted criteria. Here we show how measurement duration and timing affect these criteria and impact on the estimation of basal metabolic rate (oxygen consumption and carbon dioxide production) and standard evaporative water loss of a small nocturnal rodent. Oxygen consumption, carbon dioxide production and evaporative water loss all decreased over the duration of an experiment. Random assortment of hourly values indicated that this was an animal rather than a random effect for up to 11 h. Experimental start time also had a significant effect on measurement of physiological variables. A longer time period was required to achieve minimal carbon dioxide consumption and evaporative water loss when experiments commenced earlier in the day; however, experiments with earlier start times had a lower overall estimates of minimal oxygen consumption and carbon dioxide production. For this species, measurement duration of at least 8 h, ideally commencing between before the inactive phase at 03:00 h and 05:00 h, is required to obtain minimal standard values for physiological variables. Up to 80% of recently published studies measuring basal metabolic rate and/or evaporative water loss of small nocturnal mammals may overestimate basal values due to insufficiently long measurement duration.